1986
DOI: 10.1093/jac/18.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of erythromycin uptake and release by human lymphocytes and polymorphonuclear leucocytes

Abstract: The uptake of 14C-labelled erythromycin by human lymphocytes and polymorphonuclear leucocytes was studied. Erythromycin was concentrated by the cells. The amount of accumulated erythromycin was correlated with the cell count and was found to increase with alkaline pH and with increasing temperature of the incubation medium. The uptake of erythromycin could be reduced by compounds which inhibit cell respiration, glycolysis and (Na+-K+)membrane ATPase. Furthermore, the uptake was saturable and followed Michaelis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 0 publications
2
9
1
Order By: Relevance
“…In line with previous in vitro experiments, after the end of therapy a fast decrease of concentrations was observed for all compartments including WBCs in the present study (24). Seven days after the end of treatment, erythromycin concentrations were below the limit of detection in all compartments including WBCs, suggesting that no strong intracellular binding of erythromycin takes place (10).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous in vitro experiments, after the end of therapy a fast decrease of concentrations was observed for all compartments including WBCs in the present study (24). Seven days after the end of treatment, erythromycin concentrations were below the limit of detection in all compartments including WBCs, suggesting that no strong intracellular binding of erythromycin takes place (10).…”
Section: Discussionsupporting
confidence: 93%
“…Based on these data, one might speculate that erythromycin first rapidly penetrates into leukocytes and later, when the accumulation capacity of WBCs is saturated, the extracellular concentration increases. Indeed, saturable uptake of erythromycin by WBCs was previously described (10). In line with previous in vitro experiments, after the end of therapy a fast decrease of concentrations was observed for all compartments including WBCs in the present study (24).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in marked contrast to what we have observed with other highly concentrated antibiotics (clindamycin, erythromycin), which are promptly released from alveolar macrophages and PMNs upon removal of extracellular drug (18,26). Other investigators have also observed a rapid efflux of macrolide antibiotics (osamycin, rokitamycin, clarithromycin, and roxithromycin, in addition to erythromycin) from human PMNs, lymphocytes, and tissue culture cells (6,17,23 (25).…”
Section: Resultscontrasting
confidence: 66%
“…Potential cooperation between an antibiotic and the immune system is particularly important in patients with impaired immune function, such as patients with acquired immune deficiency syndrome. Erythromycin and macrolides show excellent penetration of polymorphonuclear leukocytes, macrophages, and lymphocytes (5,11,18,25,26). This is particularly important in infections with Legionella spp., Mycobacterium spp., Listeria spp., Brucella spp., Staphylococcus aureus, Toxoplasma spp., and Chlamydia spp., which are known to survive intracellularly.…”
Section: Macrolides and The Immune Systemmentioning
confidence: 99%